Changes of selected biochemical, physiological and densitometric parameters under low frequency vibration - Damijan, Z. (Archives of Acoustics, 2006)
The effects of low frequency vibration exposure on the humans were investigated in the Institute of Human Biophysiology of the Academy of Physical Education in Kraków. The research program involved nineteen 1200 s vibrations exposure sessions in the subsequent working days, at the same time of day for each participant. During each session, selected physiological parameters were registered before and after the exposure, the heart beat rate HR and saturation levels SpO2 were monitored on the constant basis. The research program was supported by the biochemical and densitometric analysis before and after the experiments.